G176 Public awareness of childhood, teenagers and young adult cancer signs and symptoms in great britain. (25th October 2020) - Liu, JF; Shanmugavadivel, D; Gamble, A; Stewart, A; Walker, DA
Abstract : Aims: To assess public awareness of the risks and symptoms of cancer in children and young adults under 18 in Great Britain and compare them with the published data where 60–94% of adults are aware of their cancer risks and symptoms. Methods: A face-to-face, computer-assisted opinion survey was conducted by Ipsos MORI. The population-based sample included 475 males and 525 females over the age of 18 and 26% have children aged 6–15 in the household. Questions covered perception about cumulative cancer risk (1 in 450 by the age 15 and 1 in 180 by 25), confidence in recognising signs and symptoms, recognition and perceived urgency of 42 classical signs and symptoms. Results: Over half (56%) of the respondents felt the quoted cumulative age-related cancer risks were higher than they expected. Only 32% felt confident to recognise the signs and symptoms of cancer in the age range. On average, respondents identified 14.9 out of the 42 of the classical signs and symptoms. Top ranked symptoms or signs were: 'lump, swelling in pelvis, testicle or breast' (46%), 'blood in urine or stool' 44%, 'changes to moles' 43%, 'lump or swelling in the chest wall or armpits' 41% and 'weight loss' 40%. The least recognised symptoms were early or late puberty (10%), developmental delay in young children under 2 (11%) and slow growth (13%), where 8%, 2% and 6%, respectively, felt that there was no need to discuss them with a doctor. Symptoms where more than 50% of respondents judged them as requiring medical assessment within 48 hours were: seizures/fits, blood in urine or stool, persistent vomiting, persistent fever or night sweats. Abnormal facial movements and persistent abdominal pain were added for assessment within 2 weeks. All but one of the symptoms were selected for assessment by 3 months. Conclusions: We conclude that public awareness of the risks and signs and symptoms of childhood cancer are substantially lower than awareness for adult cancer population in Great Britain. A similar survey will be conducted amongst healthcare professionals to support the development of campaign materials for a public and professional awareness programme.